Blocking TNF-α Reduces Leishmania major-Induced Hyperalgesia and Changes the Cytokine Profile in the Paw Skin of BALB/c Mice with a Potential Positive Effect on Parasite Clearance - Muriel Tahtouh Zaatar; Sara Salman; Reem Hoblos; Rabih Roufayel; Ziad Fajloun; Jean-Marc Sabatier; Marc Karam (Microbiology Research)
The course and outcome of infection with the parasitic protozoa Leishmania major depends on the host immune response which, itself, depends mainly on the cytokine milieu, especially early in the infection. It is widely accepted that INF-γ, TNF-α, and IL-12 usually favor a protective response, while IL-4, IL-5, IL-10, and IL-13 favor a pathogenic one. These and other cytokines also play a major role in Leishmania-induced hyperalgesia via two possible pathways, one involving prostaglandins and the other sympathetic amines as final mediators, preceded by a cascade of cytokines, among which TNF-α seems to play a pivotal role via a still unclear mechanism of action. This study investigates the effects of anti-TNF-α antibody (Infliximab) on L. major-induced hyperalgesia in susceptible BALB/c mice using the hot plate and tail flicks tests, as well as the levels of many cytokines in the infected paws of mice using the ELISA technique. In addition, the parasite burden was assessed using the serial dilution method. Our results show that Infliximab can reduce the induced hyperalgesia, up-regulate TNF-α, IL-1β, and keratinocyte-derived chemokine (KC), and down-regulate IL-10 and IL-17 in the paws of infected mice. Infliximab may also have beneficial effects on the prognosis of cutaneous leishmaniasis by reducing the parasite burden.